On the Practical Applicability of the Li Metal‐Based Thermal Evaporation Prelithiation Technique on Si Anodes for Lithium Ion Batteries. Issue 3 (27th November 2022) - Adhitama, Egy; Bela, Marlena M.; Demelash, Feleke; Stan, Marian C.; Winter, Martin; Gomez‐Martin, Aurora; Placke, Tobias
Abstract: Lithium ion batteries (LIBs) using silicon as anode material are endowed with much higher energy density than state‐of‐the‐art graphite‐based LIBs. However, challenges of volume expansion and related dynamic surfaces lead to continuous (re‐)formation of the solid electrolyte interphase, active lithium losses, and rapid capacity fading. Cell failure can be further accelerated when Si is paired with high‐capacity, but also rather reactive Ni‐rich cathodes, such as LiNi0.8 Co0.1 Mn0.1 O2 (NCM‐811). Here, the practical applicability of thermal evaporation of Li metal is evaluated as a prelithiation technique on micrometer‐sized Si (µ‐Si) electrodes in addressing such challenges. NCM‐811 || "prelithiated µ‐Si" full‐cells (25% degree of prelithiation) can attain a higher initial discharge capacity of ≈192 mAh gNCM‐811 −1 than the cells without prelithiation with only ≈160 mAh gNCM‐811 −1 . This study deeply discusses significant consequences of electrode capacity balancing (N:P ratio) with regard to prelithiation on the performance of full‐cells. The trade‐off between cell lifetime and energy density is also highlighted. It is essential to point out that the phenomena discussed here can further guide the direction of research in using the thermal evaporation of Li metal as a prelithiation technique toward its practical application on Si‐based LIBs. Abstract : A systematic evaluation of the practical applicability of the Li metal‐based thermal evaporation prelithiation technique on Si anodes is reported here. The practical relevance is examined in the LiNi0.8 Co0.1 Mn0.1 O2  || μ‐Si full‐cell setup. The different electrode capacity balancing (N:P ratio) is deeply investigated and the trade‐off between cell lifetime and energy density with regard to the prelithiation is highlighted.